The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1073/pnas.1520175113
|View full text |Cite
|
Sign up to set email alerts
|

Cell-type–restricted anti-cytokine therapy: TNF inhibition from one pathogenic source

Abstract: Overexpression of TNF contributes to pathogenesis of multiple autoimmune diseases, accounting for a remarkable success of anti-TNF therapy. TNF is produced by a variety of cell types, and it can play either a beneficial or a deleterious role. In particular, in autoimmunity pathogenic TNF may be derived from restricted cellular sources. In this study we evaluated the feasibility of cell-type-restricted TNF inhibition in vivo. To this end, we engineered MYSTI (Myeloid-Specific TNF Inhibitor)-a recombinant bispec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 67 publications
(57 citation statements)
references
References 45 publications
0
54
0
2
Order By: Relevance
“…Thus, biologics like the chimeric-IL-1Ra that might reduce the inflammatory process in the tumor site without reducing the patient's ability to fight infection is a desirable approach. In order to inhibit cell surface TNF, in a cell-type restricted manner, Efimov et al constructed bispecific antibody that recognizes both the F4/80 macrophage marker and the membranal TNF- α [154]. In this manner, the antibody favors binding of TNF- α on myeloid cells rather than free TNF- α or T lymphocytes derived TNF- α .…”
Section: Reducing Infections In Anti-inflammatory Biologicsmentioning
confidence: 99%
“…Thus, biologics like the chimeric-IL-1Ra that might reduce the inflammatory process in the tumor site without reducing the patient's ability to fight infection is a desirable approach. In order to inhibit cell surface TNF, in a cell-type restricted manner, Efimov et al constructed bispecific antibody that recognizes both the F4/80 macrophage marker and the membranal TNF- α [154]. In this manner, the antibody favors binding of TNF- α on myeloid cells rather than free TNF- α or T lymphocytes derived TNF- α .…”
Section: Reducing Infections In Anti-inflammatory Biologicsmentioning
confidence: 99%
“…Our study demonstrated that A20 expression on the CD56 bright subset, the key source of proinflammatory cytokines in patients with AS, was negatively correlated with IFN-γ and TNFα, indicating that the decreased A20 might increase the severity of disease, at least partly. Furthermore, monocytes or macrophages were demonstrated to be the predominant source of the proinflammatory cytokines, preferentially producing TNF-α [38][39][40]. A previous study also illustrated that NK cells, particularly the CD56 bright subset, can stimulate monocytes to produce abundant amounts of TNF-α [21].…”
Section: Discussionmentioning
confidence: 94%
“…Furthermore, monocytes or macrophages were demonstrated to be the predominant source of the proinflammatory cytokines, preferentially producing TNF-α [38][39][40]. Furthermore, monocytes or macrophages were demonstrated to be the predominant source of the proinflammatory cytokines, preferentially producing TNF-α [38][39][40].…”
Section: Discussionmentioning
confidence: 99%
“…Several MYSTIs, based on recombinant antibodies with dual specificity, were engineered and evaluated. In particular, the surface molecules F4/80 and CD11b expressed by myeloid cells were tested as the targets for the second specificity to direct anti-TNF moiety specifically to myeloid cells [84,85]. Instead of using conventional antibodies and their conjugates, we used small antigen-binding domains, called VHH, coming from a unique class of single heavy-chain antibodies in camelids [86,87].…”
Section: Toward Selective Cytokine Targetingmentioning
confidence: 99%